MANAJEMEN PELAYANAN INSTALASI FARMASI RSUD DR. MOEWARDI SURAKARTA TAHUN 2017 - Anggih Aribawa, Joko Pramono, Joko Suranto (Solidaritas, 2018)
ABSTRACT Rumusan Masalah dalam Penelitian ini adalah “Bagaimana manajemen pelayanan instalasi Farmasi RSUD dr. Moewardi. Tujuan dari penelitian ini adalah Untuk menganalisis manajemen pelayanan instalasi Farmasi RSUD dr. Moewardi Surakarta Penelitian ini merupakan penelitian deskriptif yang didukung oleh data kualitatif. Penelitian dilakukan di RSUD DR. Moewardi di Surakarta. Dari hasil penelitian dapat disimpulkan bahwa: Manajemen Pelayanan instalasi farmasi RSUD Moewardi menerapkan Fungsi-Fungsi Manajemen Pelayanan yaitu:Fungsi Perencanaan; Fungsi pengorganisasian;Fungsi Pengarahan; dan Fungsi pengawasan; . Masalah Manajemen pelayanan di Instalasi Farmasi RSUD Dr.Moewardi di antaranya : Penanganan dalam menanggapi Keluhan Para pegawai yang kurang efektif dalam Konseling Pegawai, serta ketidaksesuaian antara Standart yang dipakai dalam Pengawasan dengan Fleksibilitas Pengawasan menyebabkan menurunnya kinerja pegawai . karena itu dibutuhkan penelitian untuk membenahi Manajemen pelayanan di Instalasi Farmasi RSUD Dr.MoewardiProblem formulation in this research is “ How is The Management Services of Pharmaceutical Installation at Regional public hospital Dr. Moewardi in 2017 .the purpose of this research is to Analyzes The Management Services of Pharmaceutical Installation at Regional public hospital Dr. Moewardi in 2017. This research is a descriptive research supported by qualitative data. This research was conducted at Regional public hospital Dr. Moewardi in Surakarta. From the research results can be concluded that: The Management Services of Pharmaceutical Installation at Regional public hospital Dr. Moewardi is Implementing Service management functions Including: function of Planing, Function of Organizing,function of Directing, and Function of Controlling. The Problem that found in The Management Services of Pharmaceutical Installation at Regional public hospital Dr. Moewardi Consist of: the ineffectiveness of handling in response to the employees complaints in Employees counseling, Also Incompatibility between the Standart that used in the Controlling Functions and the Flexibility of the Controlling Functions causing a decrease in Employees Working Performance. Because of that it takes Research to fix Management Services of Pharmaceutical Installation at Regional public hospital Dr. MoewardiKeyword: Management, Pharmaceutical Installation, Regional public hospital Dr. Moewardi